Controlling in the Logistics of Transport of Autonomous Vehicles and Devices - Martin HOLUBČÍK; Jakub SOVIAR; Patrik CÁDER (Communications of International Proceedings, 2021)
In the article, we analyzed in detail the environment of autonomous vehicles and device, from a general and logistical point of view, we evaluated their advantage / disadvantage, we examined the use of this technology in practice and evaluated what procedure to maintain in their use. Logistics companies have long been trying to automate their processes and use autonomous vehicles and device to transport various products, semi-finished products, raw materials and other things. In recent years, there have been great technological advances in this area and their popularity is growing (Industry 4.0, Internet of Things, and others). Thanks to the rapid development of autonomous control technologies such as sensors, camera systems, wireless communications and software, autonomous vehicles, device and virtual assistants are becoming more accessible. There will be more and more vehicles and device with autonomous functions in transport and distribution.
Keywords: Autonomous transport. Artificial intelligence. Logistics. Management. Management Assistant. Autonomous device. Automation. UAV. ADAS. ADS. AND IN.